Congenital Anomalies of the Kidney and the Urinary Tract – Fetal Autopsy Study - Roli Joshi; Shipra Gupta; Richa Niranjan (Journal of the Scientific Society)
Objective: Congenital anomalies of the kidney and urinary tract (CAKUT) comprise a wide spectrum of disorders ranging from simple variants with no clinical significance to complex anomalies that may lead to severe complications and end-stage renal disease. This study detects urinary anomalies, its incidences, association with other systemic anomalies, and changes in their microanatomy during the antenatal period through autopsies of the aborted fetuses. Methods: A cross-sectional study of a total of 280 aborted fetuses was autopsied. The incidences of urinary anomalies which were related to the renal parenchyma, the pelvi-ureteral system and the urinary bladder, gross anomalies and changes in microanatomy were recorded in different gestational age groups, both genders and associated anomalies with other systems. Results: Ninety-four of the 280 fetuses detected with CAKUTs, the incidence was 33.57%. Polycystic kidney, hydronephrosis among renal disorders and duplicated ureter among ureteral defects were the common anomalies. Most affected fetuses were with the gestational age of 16–32 weeks (36.07%), more common in male (58.3%) fetuses with unilateral side involvement, and the most common association (8.5%) with congenital heart disease was noted. Conclusions: An early antenatal detection of these and associated anomalies has significance, as this may help in an early postnatal correct diagnosis and management to minimize adverse outcomes. The degree and the extent of the detected anomalies could also help in the decision-making regarding either the therapeutic termination or the postnatal management requirement to avoid the high rate of morbidity associated with these malformations.